THE IMPRESSION OF PROFIT QUALITY AGAINST TIMELINESS IN FINANCIAL REPORTING - Bambang Tri Wahyuono; Fetri Setyo Liyundira; Inud Danis Ikhwan Meranti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The purpose of this study was to determine the effect of the profitability and size of the company on the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016 - 2018. The data used in this study are secondary, in the form of company annual reports. The number of companies studied was 115 companies within a period of 3 years, resulting in 345 samples. This type of research is quantitative research. Where this study uses data collection methods and processes them then tested to describe the hypotheses that have been set. The selection of a sample is to use certain criteria. Data were analyzed using multiple linear regression. Based on the test results show that the profitability and size of the company significantly influence the timeliness. The test results showed that 7.1% of the variation in timeliness was explained by variations in the independent variables, namely ROA and SIZE. At the same time, the remaining 92.9% is explained by other variables not included in this research model.